1983
DOI: 10.1007/bf00285392
|View full text |Cite
|
Sign up to set email alerts
|

Homologous genes for X-linked chondrodysplasia punctata in man and mouse

Abstract: X-linked dominant chondrodysplasia punctata is a human gene defect characterized by punctate foci of epiphyseal calcification, cataracts, ichthyosis, and systematized atrophoderma. In a comparative study, the murine X-linked mutant 'bare patches' was found to display strikingly similar skeletal, ocular, and cutaneous anomalies. The human as well as the murine phenotypes occur exclusively in the female sex, apparently because the underlying mutations are lethal for male embryos. In both traits, the cutaneous le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Lens cortical "frost figure" opacities are present. Bpa is considered as a model for human X-linked syndrome chondrodysplasia punctata (Happle et al, 1983;Angel et al, 1993). The mutation vacuolated lens (vl) is mapped to mouse chromosome 1 and leads to opaque white lenses.…”
Section: Mutants Waiting For Molecular Characterizationmentioning
confidence: 99%
“…Lens cortical "frost figure" opacities are present. Bpa is considered as a model for human X-linked syndrome chondrodysplasia punctata (Happle et al, 1983;Angel et al, 1993). The mutation vacuolated lens (vl) is mapped to mouse chromosome 1 and leads to opaque white lenses.…”
Section: Mutants Waiting For Molecular Characterizationmentioning
confidence: 99%
“…The hallmark of affected females is the development hyperkeratotic eruptions in the skin at postnatal day 5 that resolve to hairless patches after 2–3 weeks [14]. They also display skeletal defects, occasional microphthalmia, and, on average, are smaller than wild type (WT) littermates at birth [15]. Mutations in the human NSDHL gene cause CHILD syndrome, a rare disorder causing early embryonic lethality in males, and unilateral skin defects and limb reduction in females [1618].…”
Section: Introductionmentioning
confidence: 99%
“…The skin lesions found in the mouse (linear pigmentary disturbances, linear arrangement of hyperkeratosis, linear absence of hair) correspond to the cutaneous markers of X-linked dominant chondrodysplasia punctata in humans. In 1983, Happle et al [18] demonstrated homology also for the skel etal and ocular abnormalities. The locus for Bpa has re cently been shown to be located between the a,-subunit of the receptor for y-aminobutyric acid (Gaba 3) and the murine X-linked visual pigment gene [19].…”
Section: Discussionmentioning
confidence: 99%